Functional Status of the Children with Cerebral PalsyAnd Their Mothers’ Psychological Status: A Cross-sectional Study - Demırhan, Esma; Eriman, Esma Ocal; Icagasıoglu, Afitap (International Journal of Human and Health Sciences (IJHHS), 2022)
a